AYAT-AYAT FILOS0FIS SEBUAH PERCIKAN “FILSAFAT TUHAN” - Rambe, Uqbatul Khair (UIN Sumatera Utara Medan, 2018)
God conveys His explanation through the verses contained in the holy book, man and in the universe. Humans who have the obligation to know and believe in God have conducted studies so as to bring up scientific studies carried by the foundations of the Qur'an and philosophy. This article aims to elaborate the verses of God with a philosophical and interpretive approach. Through a philosophical approach obtained a comprehensive understanding of religion and worldly life